2008
DOI: 10.1039/b703193a
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of234U/238U and230Th/232Th in volcanic rocks using the Neptune MC-ICP-MS

Abstract: We present a new multicollector inductively coupled plasma mass spectrometric (MC-ICP-MS) method for measuring isotopic ratios of 234 U/ 238 U and 230 Th/ 232 Th in volcanic rocks using the Thermo Fisher Neptune. Uranium isotope measurements using SRM U010 as bracketing standard produce agreement within several permil for NBL 112A, REMP-18, as well as for equilibrium rock standards. We also demonstrate that uranium standards are not appropriate for correcting thorium isotopic measurements due to differences be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
49
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 14 publications
2
49
1
Order By: Relevance
“…Our analytical methods at the WHOI facility produced uncertainties in keeping with the findings of Richter et al (2006), and as previously reported by Ball et al (2008) and Sims et al (2008b). During analysis of U isotopes using the facility's ThermoFinnigan Neptune, we calibrated SEM yield and simultaneously corrected for mass bias with standard-sample-standard bracketing to monitor SEM efficiency and measurement of the standard U010.…”
mentioning
confidence: 63%
See 4 more Smart Citations
“…Our analytical methods at the WHOI facility produced uncertainties in keeping with the findings of Richter et al (2006), and as previously reported by Ball et al (2008) and Sims et al (2008b). During analysis of U isotopes using the facility's ThermoFinnigan Neptune, we calibrated SEM yield and simultaneously corrected for mass bias with standard-sample-standard bracketing to monitor SEM efficiency and measurement of the standard U010.…”
mentioning
confidence: 63%
“…During analysis of U isotopes using the facility's ThermoFinnigan Neptune, we calibrated SEM yield and simultaneously corrected for mass bias with standard-sample-standard bracketing to monitor SEM efficiency and measurement of the standard U010. Ball et al (2008) observed that the SEM yield correction is error limiting for these analyses. Mass bias drift is corrected and SEM yield is calibrated using U010 corrections (Ball et al, 2008), and mass bias corrections are made using a linear interpolation of U010 238 U/ 236 U = 14,535 ± 149 (Sims et al, 2008b).…”
mentioning
confidence: 99%
See 3 more Smart Citations